2019
DOI: 10.1016/j.ejvs.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of revascularization outcomes of infrainguinal chronic limb-threatening ischemia

Abstract: Background: The optimal strategy for revascularization in infrainguinal chronic limb-threatening ischemia (CLTI) remains debatable. Comparative trials are scarce, and daily decisions are often made using anecdotal or low-quality evidence. Methods: We searched multiple databases through May 7, 2017, for prospective studies with at least 1-year follow-up that evaluated patient-relevant outcomes of infrainguinal revascularization procedures in adults with CLTI. Independent pairs of reviewers selected articles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 19 publications
0
45
1
Order By: Relevance
“…Most current reconstructive procedures consist of interposition of the vessel defect with autologous or synthetic grafts because en bloc resection usually necessitates resection of a long segment of vessels. Previous review articles about obstructive arterial disease demonstrated that graft selection could influence the long‐term limb‐salvage rate, and autologous graft is superior to synthetic graft in patency (Almasri et al, ; Klinkert, Post, Breslau, & van Bockel, ). However, in sarcoma surgery in contrast to obstructive arterial disease, there are some specific situations, such as requirement of a relatively short graft, not atherosclerotic artery, and postoperative formation of arterial collateral.…”
Section: Discussionmentioning
confidence: 99%
“…Most current reconstructive procedures consist of interposition of the vessel defect with autologous or synthetic grafts because en bloc resection usually necessitates resection of a long segment of vessels. Previous review articles about obstructive arterial disease demonstrated that graft selection could influence the long‐term limb‐salvage rate, and autologous graft is superior to synthetic graft in patency (Almasri et al, ; Klinkert, Post, Breslau, & van Bockel, ). However, in sarcoma surgery in contrast to obstructive arterial disease, there are some specific situations, such as requirement of a relatively short graft, not atherosclerotic artery, and postoperative formation of arterial collateral.…”
Section: Discussionmentioning
confidence: 99%
“…Devices with approximately 150 to 180 cm working lengths are required to treat infrapopliteal PAD. 38 A recent meta-analysis by Almasri et al 39 examining revascularization outcomes of infrainguinal CLI (44 studies, 8,602 total patients) showed that drug-eluting stents have improved patency over bare metal stents in infrapopliteal arteries (73 vs. 50%) and comparable to balloon angioplasty (66% primary patency) at 1 year. There are no stents or drug-coated balloons that reach this distance.…”
Section: Infrainguinal Diseasementioning
confidence: 99%
“…timal durability of the associated devices, EVT has yet to provide clinical results that are equivalent to those of surgical reconstruction [6][7][8] The importance of surgical therapy has been consistently highlighted in the latest guidelines particularly because patients frequently require reintervention after EVT 5) . In fact, the Surgical Reconstruction Versus Peripheral Intervention in Patients With Critical Limb Ischemia (SPIN-ACH) study recently found that CLTI patients undergoing EVT had a higher risk of reintervention than a matched population undergoing surgical reconstruction, although no significant differences were observed with regard to major amputation or all-cause mortality 7) .…”
Section: Introductionmentioning
confidence: 99%